Inhibitory effect of LSOPC on AGEs formation and sensory quality in cookies - Wu, Qian; Tan, Jiangying; Qin, Jiabin; Chen, Ziting; Li, Bing; Xu, Jianhua; Jiao, Weiting; Feng, Nianjie (Frontiers in Nutrition, 2022)
At the conclusion of the Maillard reaction (MR), free amino groups of proteins, amino acids, or lipids with the carboxyl groups of reducing sugars to form stable molecules known as advanced glycation end products (AGEs), which hasten aging and may potentially be the root cause of a number of chronic degenerative diseases. According to researches, lotus seedpod oligomeric procyanidins (LSOPC), a premium natural antioxidant produced from lotus waste, can be included in cookies to improve flavor and lower the risk of illnesses linked to AGEs. In this work, we used cookies without LSOPC as a control to examine the effects of adding various concentrations of LSOPC (0, 0.05, 0.1, 0.2, and 0.4%) on the AGEs formation and the sensory quality in cookies. The amounts of AGEs and N-ε-carboxymethyl lysine (CML) decreased with the increase of LSOPC concentration, indicating that the concentration of LSOPC was positively correlated with the ability to inhibit AGEs formation. It was also demonstrated that the amount of antioxidant capacity of the cookies increased significantly with the increase of LSOPC concentration. On the other hand, the chromaticity, texture, electronic nose, and other aspects of the cookies’ sensory attributes were also evaluated. The color of the cookies deepened and the flavor varied as LSOPC added content increased. The sensory quality of the cookies was examined, and the findings indicated that LSOPC would somewhat improve that quality. These findings implied that AGEs formation could be decreased in cookies while also enhancing their sensory quality by adding LSOPC.